Identification of tooth traces from a Cretaceous (Maastrichtian) Edmontosaurus annectens bonebed in the Lance Formation, Wyoming, U.S.A. - Bethania C. T. Siviero; Elizabeth Rega; Matthew A. McLain; Leonard R. Brand; David Nelsen; Art V. Chadwick (PLoS ONE, 2026)
Identifying the origin of perforating lesions on fossil bone is often difficult, and many are considered tooth traces, in spite of more likely and more parsimonious etiologies. Much of this confusion stems from tooth trace criteria that are ambiguous when the context for the lesions is not considered. Mistaken identification of tooth traces has led to misleading interpretations of animal behavior. This study of tooth traces on fossil bones critically reviews previous criteria and applies them to assessing bones from an Edmontosaurus annectens bonebed within the Lance Formation, Wyoming, USA. Of the 3013 bones examined, thirteen bones had features indicative of tooth traces based on gross appearance. Of these, one bone had perforations determined to have a different etiology. Twelve bones had traces attributed to tooth marks, including four bones with Knethichnus parallelum and Linichnus serratus ichnotaxa. Tyrannosaurus rex was identified as the likely inflictor of traces attributable to both ichnotaxa, by comparison of denticle density of carnivore teeth within the bonebed with striation/serration density of the traces. The importance of context in the analysis of perforating lesions on fossil bones is shown through the mistaken identification of features such as neurovasculature foramina and lesions associated with pathology as tooth traces. This study contributes to the literature on biting behavior and refines the criteria used to identify perforations caused by bite marks. The application of these refined criteria also proved useful in accurately identifying tooth traces on bone. This, in turn, enhances the guidelines for recognizing perforations as tooth traces and encourages further research on this topic.